2004
DOI: 10.1128/aac.48.10.3765-3772.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ertapenem Pharmacokinetics and Impact on Intestinal Microflora, in Comparison to Those of Ceftriaxone, after Multiple Dosing in Male and Female Volunteers

Abstract: The pharmacokinetics of ertapenem and ceftriaxone were investigated in an open, randomized, two-period crossover study after single-and multiple-dose administration in 10 healthy volunteers (five women and five men). Both antibiotics were administered intravenously once daily for 7 days at dosages of 1 g (ertapenem) and 2 g (ceftriaxone). The concentrations of the antibiotics in serum and urine were quantified by the agar well diffusion method bioassay and, in addition, for ertapenem only, by liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
3
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 17 publications
(23 reference statements)
8
60
3
3
Order By: Relevance
“…Second, we measured colonization by only E. coli rather than the whole intestinal microbiota, which includes anaerobic microflora. Previous studies have suggested that ceftriaxone treatment may also significantly decrease the intestinal density of anaerobes (34,45), and intestinal anaerobic microflora are more likely to be responsible for colonization resistance (5,6,31). Third, the intrinsic physiological differences between rats and humans may result in disparate microbiological and pharmacological responses, thus limiting the external validity of the conclusions of this study.…”
Section: Discussionmentioning
confidence: 49%
“…Second, we measured colonization by only E. coli rather than the whole intestinal microbiota, which includes anaerobic microflora. Previous studies have suggested that ceftriaxone treatment may also significantly decrease the intestinal density of anaerobes (34,45), and intestinal anaerobic microflora are more likely to be responsible for colonization resistance (5,6,31). Third, the intrinsic physiological differences between rats and humans may result in disparate microbiological and pharmacological responses, thus limiting the external validity of the conclusions of this study.…”
Section: Discussionmentioning
confidence: 49%
“…Stool samples for which a zone of inhibition was observed around the disc, following overnight incubation at 37°C, were determined to have antibacterial activity. Studies in which volunteers were experimentally exposed to antibiotics have shown that this test is always negative for samples taken before drug exposure began (14).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of patients with broad-spectrum antimicrobial agents predisposes to the emergence of resistant bowel flora during therapy (1,4,12,22,23,26,27). Resistant organisms can emerge through genetic mutation or induction, can be acquired exogenously, or, if already present in undetectably low concentrations, may overgrow under selective pressure.…”
Section: Discussionmentioning
confidence: 99%